(untitled) (LEARNing Landscapes, 2021)
This paper explores how students connect meaningfully with theory through the aesthetic experiences of problem solving together in the context of a workshop. It can be challenging for students studying design in university programs to understand how theory is relevant, when applied in practical design studio activities. In the colour workshop presented, students participate in brainstorming exercises to create proposals. Theory is made meaningful through learning activities, including a creative brainstorming session animated by both teachers and industry guests. The experience described was enthusiastically received, with the academia-industry collaboration providing a valuable platform for knowledge exchange both among students and teachers.